Long‐term follow‐up and combined Phase 2 results of eprenetapopt and azacitidine in patients with TP53 mutant MDS/AML - David A. Sallman; Rami S. Komrokji; Amy E. Dezern; Marie Sebert; Guillermo Garcia‐Manero; Ramy Rahmé; Eric S. Winer; Jacqueline Lehmann‐Che; Gail J. Roboz; Isabelle Madelaine; Mikkael A. Sekeres; Pierre Peterlin; et al. (HemaSphere)
Abstract TP53 gene mutations (mTP53) represent a distinct molecular cohort with poor outcomes. Eprenetapopt (APR‐246) is a novel, first‐in‐class small molecule that reactivates p53 and targets cellular redox balance, ultimately inducing apoptosis and ferroptosis in mTP53 cancer cells. This is a multicenter, international collaboration of the US myelodysplastic syndromes/neoplasms (MDS) clinical research symposium and the Groupe Francophone des Myelodysplasies (GFM) of hypomethylating agents‐naïve mTP53 higher risk MDS and oligoblastic acute myeloid leukemia (AML; ≤30% blasts; NCT03072043/NCT03588078). Patients received eprenetapopt 4500 mg iv (Days 1–4) + azacitidine 75 mg/m2 sc/iv × 7 days in 28‐day cycles. The primary objective was the complete remission (CR) rate by International Working Group (IWG) 2006 criteria. In total, 100 patients were enrolled with a median age of 68 years (34–87; 47% male). Febrile neutropenia occurred in 37% of patients. Thirty‐ and 60‐day mortality was 1% and 7%, respectively. By intention‐to‐treat, overall response rate by IWG was 69% with 41% CR. The median duration of CR was 10.2 months (95% CI 8.7–11.8). With a median follow‐up of 52 months, median overall survival (OS) was 11.8 months (95% CI 9.4–14.3). Although allogeneic hematopoietic cell transplantation (allo‐HCT) was borderline predictive of OS in the overall cohort by landmark analysis (14.7 vs. 14.4 months; P = 0.046), OS was significantly improved in allo‐HCT patients based on CR/TP53 next‐generation sequencing (NGS) negativity (P = 0.00085; 2‐year OS of 54%). In this international, combined analysis of Phase 2 eprenetapopt + azacitidine patients, the combination was well‐tolerated with synergistic response rates in mTP53 MDS/AML. Quality of response and NGS negativity strongly predicted OS, particularly in the setting of allo‐HCT, validating NGS clearance as a critical biomarker of allo‐HCT outcomes in mTP53 patients.